The gap between heritage branding and visual implementation: A case study of Sarinah Braga - Apriani, Destia; Soewardikoen, Didit; Sudarisman, Irwan (International Journal of Culture and Art Studies, 2026)
This study examines the gap between the intended heritage branding strategy and its visual implementation at the Sarinah Braga Building in Bandung, Indonesia, a historic commercial property undergoing revitalization. While heritage branding is widely adopted to strengthen place identity, discrepancies often emerge between strategic intentions and their material visual expression. This research aims to identify key factors contributing to such disparities and to explore differing stakeholder perceptions of the building’s visual identity. A qualitative case study approach was employed. Data were collected through in-depth interviews with four stakeholder groups—management, tenants, heritage community representatives, and visitors—supported by direct observation of visual elements and analysis of relevant documents. The data were analyzed using thematic analysis to identify recurring patterns, tensions, and inconsistencies between branding objectives and visual execution. The findings indicate a significant misalignment between heritage branding goals and visual implementation. Management primarily emphasizes historical preservation and symbolic continuity, whereas tenants prioritize commercial visibility and market appeal. These conflicting interests result in fragmented visual expressions that weaken the building’s historical coherence. Visitors acknowledge the cultural and historical significance of Sarinah Braga but perceive its visual identity as insufficiently distinctive and poorly reflective of its heritage value. This study offers practical implications for heritage site managers seeking to formulate cohesive visual guidelines that reconcile preservation imperatives with commercial demands. Theoretically, it contributes to place branding and heritage studies by demonstrating the importance of multi-stakeholder perspectives in bridging the gap between strategic branding intentions and visual implementation in heritage buildings.